The Influence of School Environment on Student Character in Class VI of 96 Buton State Elementary School, Buton Regency - Silvia Maharani; Suarti; Faslia (AIQU: Journal Multidiscipliner of Science, 2024)
The problem in this study is the influence of the school environment on the character of grade VI students of Elementary School 96 Buton. This study aims to determine the influence of the school environment on the character of grade VI students of Elementary School 96 Buton. The data collection instrument is in the form of a questionnaire. The sampling technique in this study is the saturated sampling technique with a sample size of 21 students. The results obtained in this study are that there is a significant relationship of 0.704 and the influence of the school environment on the character of students at Elementary School 96 Buton is in the high category with a correlation interpretation of 0.60-0.799. This is indicated by the results of the product moment calculation, which is 0.704. While through the t test, the t table is obtained at a significance level of 5% = 1.729, this means that the calculated t> t table with an accumulated value of 6.722> 1.729. Thus, the results of the study are significant between the school environment and student character.